POLA PEMBERIAN MAKAN, PEMBERIAN ASI EKSKLUSIF, ASUPAN PROTEIN DAN ENERGI, SEBAGAI PENYEBAB STUNTING DI DESA GROGOL PONOROGO - Ratih Dwilestari Puji Utami (Jurnal Keperawatan Malang, 2020)
Malnutrition is one of the problems related to child growth that has not been resolved until now, such of stunting. Stunting is a condition in which the child's growth, especially height or body length, has z-score less than -2 SD. The purpose of this study to identify the causes of stunting in children under five in Grogol village using a cross-sectional quantitative study approach. 67 samples through stratified random sampling and filling questionnaire. The analysis showed that there was a relationship between the incidence of stunting with feeding pattern (p = 0.001), protein intake (p = 0.001), history of exclusive breastfeeding (p = 0.002), and energy intake (p = 0.003). The conclusion of this study, feeding pattern has the strongest relationship with the incidence of stunting and very short stunting in toddlers.